Diet and temperature modify the relationship between energy use and ATP production to influence behavior in zebrafish (Danio rerio). Issue 14 (21st June 2021) - Le Roy, Amélie; Mazué, Geoffrey P. F.; Metcalfe, Neil B.; Seebacher, Frank
Abstract: Food availability and temperature influence energetics of animals and can alter behavioral responses such as foraging and spontaneous activity. Food availability, however, is not necessarily a good indicator of energy (ATP) available for cellular processes. The efficiency of energy transduction from food‐derived substrate to ATP in mitochondria can change with environmental context. Our aim was to determine whether the interaction between food availability and temperature affects mitochondrial efficiency and behavior in zebrafish ( Danio rerio ). We conducted a fully factorial experiment to test the effects of feeding frequency, acclimation temperature (three weeks to 18 or 28°C), and acute test temperature (18 and 28°C) on whole‐animal oxygen consumption, mitochondrial bioenergetics and efficiency (ADP consumed per oxygen atom; P:O ratio), and behavior (boldness and exploration). We show that infrequently fed (once per day on four days per week) zebrafish have greater mitochondrial efficiency than frequently fed (three times per day on five days per week) animals, particularly when warm‐acclimated. The interaction between temperature and feeding frequency influenced exploration of a novel environment, but not boldness. Both resting rate of producing ATP and scope for increasing it were positively correlated with time spent exploring and distance moved in standardized trials. In contrast, behavior was not associated with whole‐animal aerobic (oxygen consumption) scope, but exploration was positively correlated with resting oxygen consumption rates. We highlight the importance of variation in both metabolic (oxygen consumption) rate and efficiency of producing ATP in determining animal performance and behavior. Oxygen consumption represents energy use, and P:O ratio is a variable that determines how much of that energy is allocated to ATP production. Our results emphasize the need to integrate whole‐animal responses with subcellular traits to evaluate the impact of environmental conditions on behavior and movement. Abstract : Food availability and temperature influence energetics of animals and can alter behavioral responses. We show that infrequently fed zebrafish have greater mitochondrial efficiency than frequently fed animals, particularly when warm‐acclimated. The interaction between temperature and feeding frequency influenced exploration of a novel environment, but not boldness.